Prenatal bonding and early emotion regulation in infancy and toddlerhood (0–36 months): a systematic review of developmental associations, psychological mediators, and contextual moderators - Cervellione, Brenda; Lombardo, Ester Maria Concetta; Geraci, Silvia; Iacolino, Calogero (Frontiers in Psychology, 2025)
IntroductionPrenatal bonding is increasingly recognized as a foundational process for postnatal development, particularly in shaping infants’ emerging emotion regulation. This review aimed to synthesize empirical evidence on the association between prenatal bonding and early emotion regulation capacities in infancy and toddlerhood (0–36 months).MethodsFollowing PRISMA 2020 guidelines, PubMed, EBSCOhost, and Scopus were systematically searched for English-language studies published between 2015 and 2025. Eligible studies assessed prenatal bonding—primarily maternal, with limited paternal inclusion—and postnatal emotion regulation outcomes in children aged 0–36 months. Methodological quality was appraised narratively due to substantial heterogeneity in designs, measures, and outcomes; a structured narrative synthesis was therefore undertaken.ResultsFourteen studies met inclusion criteria; eleven constituted the primary synthesis set (prenatal measures with outcomes ≤ 36 months), and three were considered contextually. Across studies, higher-quality prenatal bonding—particularly in the maternal domain—was associated with more favourable early regulatory indicators, notably lower negative affectivity and greater soothability. Evidence for attentional regulation and broader socioemotional adjustment was promising but more variable. Maternal mental health and sociodemographic factors emerged as consistent moderators. Although only a minority of studies included fathers, preliminary findings suggest possible additive paternal contributions.DiscussionFindings underscore the developmental significance of prenatal bonding and the need for theory-driven, multimethod longitudinal research using developmentally sensitive measures and more diverse samples, including paternal cohorts.